Dynamics Implementation Comprehensive Guidance and Counseling Program : Challenges and Opportunities in Indonesia - M. Khoirudin Jalil (Jurnal Pengetahuan dan Pendidikan, 2025)
Education in Indonesia faces complex challenges in providing effective and inclusive guidance and counseling (GC) services. This research aims to analyze the dynamics of implementing a comprehensive GC program in Indonesia, identify the challenges faced, and explore opportunities that can be leveraged to enhance the effectiveness of GC services. The method used includes a literature study. The research findings indicate that there is a significant gap between national GC policies and field practices. Factors such as lack of resources, inadequate training for counselors , and low awareness of the importance of GC are major obstacles. However, the research also found untapped opportunities, such as the use of information technology, collaboration with educational stakeholders, and the development of an adaptive GC curriculum. The implementation of a comprehensive GC program in Indonesia requires a holistic and collaborative approach. The government, educational institutions, and the community must work together to create a supportive environment for the development of quality GC. This study recommends the integration of technology in GC services, the enhancement of counselor competencies through continuous training, and the development of responsive policies to student needs.